Servicescape dan Pengaruhnya Terhadap Kepuasan Pelanggan: Studi Pada Konsumen Eduplex Bandung - Ainun, Azmi Mutia; Setiawardani, Maya (Jurnal Riset Bisnis dan Investasi, 2019)
Lifestyle communities are growing, have an impact on people's lives in fulfilling his needs.One of them, namely the need for food. To meet the needs of the food, people are more likely to go to a fast-food restaurant or Cafe. Specifically for the cafe, at this time many cafes are there in the city of Bandung stand not only to put forward products are sold, but also very attentive to the comfort of a given place.The purpose of this research is to know the servicescape and its effect on customer satisfaction at the Eduplex in Bandung.The sample in this study i.e. as many as 117 people respondents with the method of analysis used a classic assumption test, i.e. an analysis of descriptive statistics, correlation and simple linear regression, simple, the coefficient of determination and test hypotheses.